Consumer Behavior towards Mobile Phones: A Look at the Product and Technology - Shamsuddeen, Babangida Umar (2013)
In the mobile phone industry today, the success and failure of any company largely depends on its ability to identify its customer’s diverse needs and wants, particularly when teenagers form a significant portion of its customers. This study identifies consumer preference toward product attribute of a mobile phone and acceptance of the mobile technology. These preferences are influenced by the technological advancement been witnessed in the mobile phone industry, the evolution of technology to the 4G it is today. Mobile phone companies in the world need to understand the teenage consumers’ perception towards the 3 key elements in product attribute i.e. Product quality, features, style and designs, and they need to understand the importance of the elements of the Unified theory of acceptance and use of technology (UTAUT) model so that the companies will know how their potential customers feel about acceptance of technology. Various studies have reported that customer satisfaction is often influenced by Product attribute. The intention to purchase, be it the first unit or repurchase is more often than not influenced by high quality, feature packed models and being the youth as they are, consumers are intrigued by the style and designs of each brand and model. The eight dimensions of product quality have significant roles in consumer’s purchasing behavior. The study of correlation between product attribute, UTAUT Model with customer satisfaction helps mobile phone companies to stay ahead of competition by coming out with the best quality, most advanced features and the most in fashion styling and designs. The findings will have to be analyzed for the data collected to be useful to anyone. Demographic profiling, analysis of gender perceptions, consumer preferences towards product attributes and UTAUT Model are among the statistical analysis to be performed. Regression analysis is used to determine any significant difference of the Hypothesis while the results might be adopted in product development programs various mobile phone companies thereby satisfying consumer preference.